The development of British monetary policy, 1951 - SAYERS, R.S. (PSL Quarterly Review, 2014)
The article deals with British monetary policy mainly from a technical standpoint. A summarised description of the general mechanism of the “control of borrowing and investment” since the war, of the part played by the banks - which it is difficult to assess in precise terms - and of the measures taken after the change of government in the autumn of 1951 is provided. According to the author, such measures have marked “no revolution in policy”… “no overturn of the ruling doctrines”. Nevertheless, he states quite clearly that “a number of developments in the next year or so will force the authorities to take further steps in one direction or another”. JEL: E52, E58